2015
DOI: 10.1016/j.actbio.2015.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Tumor mitochondria-targeted photodynamic therapy with a translocator protein (TSPO)-specific photosensitizer

Abstract: Photodynamic therapy (PDT) has been proven to be a minimally invasive and effective therapeutic strategy for cancer treatment. It can be used alone or as a complement to conventional cancer treatments, such as surgical debulking and chemotherapy. The mitochondrion is an attractive target for developing novel PDT agents, as it produces energy for cells and regulates apoptosis. Current strategy of mitochondria targeting is mainly focused on utilizing cationic photosensitizers that bind to the negatively charged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 46 publications
(52 reference statements)
1
48
0
1
Order By: Relevance
“…42 High levels of ROS can disrupt the mitochondrial permeability transition pore and destroy the integrity of the mitochondrial membrane, resulting in immediate dissipation of mitochondrial transmembrane potential and osmotic swelling of the mitochondrial matrix. 43,44 Once …”
Section: Discussionmentioning
confidence: 99%
“…42 High levels of ROS can disrupt the mitochondrial permeability transition pore and destroy the integrity of the mitochondrial membrane, resulting in immediate dissipation of mitochondrial transmembrane potential and osmotic swelling of the mitochondrial matrix. 43,44 Once …”
Section: Discussionmentioning
confidence: 99%
“…TSPO-targeted PS, IR700DX-6T [32], and CB 2 R-targeted PS, IR700DX-mbc94 [31] (Figure 1), which share the same PS (IR700DX), were synthesized using previously reported methods. We first evaluated ROS production from IR700DX-mbc94 and IR700DX-6T upon light irradiation using singlet oxygen sensor green (SOSG).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other types of breast cancer, those with triple negative breast cancer (TNBC) have a poorer survival rate. Therefore, treatment of TNBC represents a great clinical challenge; (2) In our recent study, we found that TSPO-targeted PDT was effective in treating MDA-MB-231 cells and tumors in a target-specific manner [32]. In this study, we were interested in investigating whether adding CB 2 R-PDT to TSPO-PDT would further improve the therapeutic effect; (3) Although MDA-MB-231 cells express CB 2 R at a relatively low level, the binding affinity of IR700DX-mbc94 is much higher than IR700DX-6T (K D = 42 nM for IR700DX-mbc94 vs 1.9 μM for IR700DX-6T) [31, 32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photodynamic therapy utilizing an 18 kDa mitochondrial translocator protein target by administering IR700DX-6T induced apoptosis in MDA-MB-231 breast cancer cells [13].…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%